Perancangan Sistem Informasi Iklan Produk Halal Mui Berbasis Mobile Web Menggunakan Multimedia Interaktif - Barany Fachri (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Advertising is essentially one type of communication that other people are doing, turning in the sense of changing attitudes, traits, and behavior of people or people (communicant) in accordance with the will of the initiator of communication. Interactive Multimedia is a multimedia equipped with controller tools that can be operated by the user so that users can choose what is desired for the next process.